2022
DOI: 10.1002/mds.29133
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction betweenHLA‐DRB1and Smoking in Parkinson's Disease Revisited

Abstract: EP1802749 (A2) KASPP (LRRK2) gene, its production and use for the detection and treatment of neurodegenerative disorders issued. A. E. reports grants from ANR, The Michael J. Fox foundation, Plan Ecophyto (French Ministry of Agriculture), and France Parkinson, outside the submitted work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the context of genetic association studies, a parallel effort focused on direct association with HLA polymorphisms to understand the mechanisms in which HLA molecules impact disease susceptibility and severity. These studies have identified protective and risk HLA alleles, such as HLA-DRB1*15:01 in multiple sclerosis (Moutsianas et al 2015), HLA-DRB1*09:01 with tIgE levels in asthma (Vince et al 2020b), specific HLA-DQB1 amino acids in hepatitis C virus infection (Valencia et al 2022), or the HLA-DRB1 valine 11 in Parkinson's disease (Domenighetti et al 2022), among many others. The five most polymorphic HLA genes (HLA-A, HLA-B, HLA-C, HLA-DQB1, and HLA-DRB1) are exceptionally diverse, with almost 30,000 alleles combined (Robinson et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of genetic association studies, a parallel effort focused on direct association with HLA polymorphisms to understand the mechanisms in which HLA molecules impact disease susceptibility and severity. These studies have identified protective and risk HLA alleles, such as HLA-DRB1*15:01 in multiple sclerosis (Moutsianas et al 2015), HLA-DRB1*09:01 with tIgE levels in asthma (Vince et al 2020b), specific HLA-DQB1 amino acids in hepatitis C virus infection (Valencia et al 2022), or the HLA-DRB1 valine 11 in Parkinson's disease (Domenighetti et al 2022), among many others. The five most polymorphic HLA genes (HLA-A, HLA-B, HLA-C, HLA-DQB1, and HLA-DRB1) are exceptionally diverse, with almost 30,000 alleles combined (Robinson et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of genetic association studies, a parallel effort focused on direct association with HLA polymorphisms to understand the mechanisms in which HLA molecules impact disease susceptibility and severity. These studies have identified protective and risk HLA alleles, such as HLA‐DRB1 * 15:01 in multiple sclerosis, 26 HLA‐DRB1 * 09:01 with tIgE levels in asthma, 27 specific HLA‐DQB1 amino acids in hepatitis C virus infection, 28 or the HLA‐DRB1 valine 11 in Parkinson's disease, 29 among many others. The five most polymorphic HLA genes ( HLA‐A , HLA‐B , HLA‐C , HLA‐DQB1 , and HLA‐DRB1 ) are exceptionally diverse, with almost 30,000 alleles combined 30 .…”
Section: Introductionmentioning
confidence: 99%

Optimal population‐specific HLA imputation with dimension reduction

Douillard,
dos Santos Brito Silva,
Bourguiba‐Hachemi
et al. 2023
HLA
Self Cite